The matador's cape: America's reckless response to terror - Holmes, Stephen (Cambridge Univ. Press, 2007)
Introduction -- Did religious extremism cause 9/11? -- Why military superiority breeds illusions -- How the war was lost -- Radicals trapped in the past -- A self-inflicted wound -- Searching for a new enemy after the Cold War -- Humanitarianism with teeth -- The war of the liberals -- The neo-conservative intifada -- Liberalism strangled by war -- The unilateralist curse -- Battling lawlessness with lawlessness -- The infallibility trap -- Conclusion